Effect of Spot-Welding Current-Cycle for Medium Carbon Steel And Stainless Steel on Mechanical Properties - J.Mahmod, Nawzad; Sh. Hasan, Aysha; A.Hussein, Ahmed; M. Ali, Obed (International Journal of Engineering and Technology, 2018)
Spot welding involves the joining of two or more plate metals in localized areas where melting and jointure of a little volume of fabric happens from heating caused by resistance to the passage of an electrical current. This process is typically used for obtaining a lap joint of plate metal parts. In this work, stainless steels and medium carbon steel were used. Three rules for welding set-up, lowest tap on the fastening electrical device, highest % current setting on the weld management and shortest weld time setting on the weld management were adopted. Experiments conducted to show the effect of these variables on the welding diameter and tensile strength for each sample for medium carbon steel and stainless steel separately and joining both metals together by spot welding. The results show that the utmost durability was at stainless steel specimens and minimum tensile strength was at medium carbon steel specimens. Furthermore, the obtained results showed that the maximum heat generated was at stainless steel specimens and minimum heat generated values was at medium carbon steel specimens for all current dependent in this work. Meanwhile, slight effect of heat generated on the spot diameter for the current of 10.6 & 5.3 kA, and so significant effect on the spot diameter for the last current (2.3kA).Â Â Â